How important is the real exchange rate for exports and growth? - Robert A. Blecker (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
Economists have long debated whether the real exchange rate (RER) has a significant impact on export performance and output growth. Some claim that export performance depends only on nonprice competition and the RER is irrelevant to long-run growth, whereas others argue that the RER is a key variable for promoting long-run economic development. Neither extreme view is supported by recent empirical evidence. Most econometric studies find significant effects of RERs on exports and growth, but subject to numerous qualifications. For example, RER effects on exports differ by type of goods exported, while the negative effects of overvaluation on growth may be stronger than the positive effects of undervaluation. Even if RER effects on growth rates are found only for medium-run transitions, these may imply a long-run impact on levels of output.
Keywords: F43; O24; F31; O19; 330; real exchange rate; economic growth; overvaluation; export performance; structural change; traverse